Analysis of the Marketing Strategy for Safety Gloves Using the SWOT Method at PT Prisma Alfath Sejahtera - Raesha Bayka Putri; Apid Hapid Maskum; Naufal Rabbani Sumitra (Jurnal Serambi Engineering, 2026)
Increasing competition in the Personal Protective Equipment (PPE) distribution industry requires companies to develop effective marketing strategies to enhance competitiveness and expand market share. PT Prisma Alfath Sejahtera, a safety glove distributor, faces several challenges, including growing market competition, limited digital marketing implementation, and changing purchasing behavior among industrial customers. This study aimed to formulate an appropriate marketing strategy by identifying the internal and external factors influencing the company's marketing performance. A descriptive qualitative approach was employed using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis method. Data were collected through direct observation, documentation, market analysis, and a review of relevant literature. The findings indicate that the company's primary strengths include high-quality products, competitive pricing, and responsive customer service, while its main weaknesses are limited digital marketing capabilities and the absence of an integrated customer relationship management system. Externally, increasing demand for Personal Protective Equipment (PPE), industrial expansion, and stricter occupational health and safety regulations provide significant business opportunities despite intense market competition.